Physiological and Biological Changes in the Underground Shoots of White Cinquefoil and Potentilla alba L. and Snowdrop Galanthus nivalis L. during Wintering at Introduction - В. В. Кондратьева; М. В. Семенова; Т. В. Воронкова; О. В. Шелепова; Н. Н. Данилина (Plant Varieties Studying and Protection)
Water-soluble carbohydrates, cytokinins, ABA, salicylic acid and microelements content's dynamics in wintering underground organs of P.alba and G.nivalis were studied. Correlation between substance's level and air temperature, ground freezing depth, snow layer thickness fluctuations was determined. The role of phytohormons and free sugars in adaptive potential realization are discussed.